Breastfeeding duration and eczema risk in the Avon Longitudinal Study of Parents and Children. (24th May 2012) - Abd, A; Henderson, J; Northstone, K; Seddon, P; Palmer, C; Mukhopadhyay, S; Rogers, I
Abstract : Aims: The literature on the associations between breastfeeding and eczema prevalence is conflicting. Early reviews of the literature found that breastfeeding was associated with a reduced risk of eczema, but several recent studies have suggested that breastfeeding may increase the risk of atopic disorders at older ages. A positive association between breastfeeding and eczema risk might reflect reverse causation (longer breastfeeding of at risk children in response to early eczema symptoms). However, few studies have been able to account for the influence of early atopic symptoms on the association between breastfeeding and eczema. Here, we investigate the association between breastfeeding duration and eczema accounting for the effect of early rash on breastfeeding practice. Methods: This study used data collected as part of the Avon Longitudinal Study of Parents and Children, a geographically-based cohort study of children born in the Bristol area in 1991-92. Information on breastfeeding duration was obtained prospectively by questionnaire, information on early eczema (up to age 42 months) was obtained by parental report of rash at two time points in questionnaires completed at 6, 18, 30 and 42 months post-natal. Information on eczema at age 7-8 year was from observations of flexural dermatitis at research clinics attended by children at this age. Results: Table 1 shows the odds ratios for early eczema according to duration of breastfeeding. Risk of early eczema was significantly higher in ever versus never breastfed children (OR 1.43 95% CI 1.26, 1.61), and there was evidence of increased eczema risk with increasing breastfeeding duration. This association persisted on adjustment for potential confounders including parental education and history of atopy, and on exclusion of children with symptoms of rash in the first six months. There was a similar association with late eczema in unadjusted analysis, but this was lost on adjustment for potential confounders. Conclusion: In this study we found no evidence that breastfeeding protects against eczema. On the contrary there was more early eczema among infants breastfed for longer. This association was not explained by changes in breastfeeding practice associated with parental atopy or with symptoms of rash in the first six months.